2022
DOI: 10.1001/jamanetworkopen.2022.6019
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Installing Barriers at Bridge and Cliff Sites for Suicide Prevention in Australia

Abstract: IMPORTANCEInstallation of barriers has been shown to reduce suicides. To our knowledge, no studies have evaluated the cost-effectiveness of installing barriers at multiple bridge and cliff sites where suicides are known to occur. OBJECTIVE To examine the cost-effectiveness of installing barriers at bridge and cliff sites throughout Australia. DESIGN, SETTING, AND PARTICIPANTSThis economic evaluation used an economic model to examine the costs, costs saved, and reductions in suicides if barriers were installed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“… 50 Structural changes to bridges to restrict access have been found to be effective in some studies. 51 Regardless of the means restriction strategy identified, of importance is that the method identified is a high contributor to suicide in the area; the suitability of means restriction and elimination of the method should then be considered, as well as the social impact of placing such restrictions. 52 …”
Section: Discussionmentioning
confidence: 99%
“… 50 Structural changes to bridges to restrict access have been found to be effective in some studies. 51 Regardless of the means restriction strategy identified, of importance is that the method identified is a high contributor to suicide in the area; the suitability of means restriction and elimination of the method should then be considered, as well as the social impact of placing such restrictions. 52 …”
Section: Discussionmentioning
confidence: 99%
“…In our sampled tweets, although a few people complained about the closure of Vessel due to the suicide incidents and expressed their wish to visit it in the future (Theme 3) , no one argued against the installation of barriers for aesthetic reasons; in fact, this was the second most popular suggestion, closely following the demand for dismantling the structure in the fourth case. Regarding the economic argument surrounding raising barriers, although the price is indisputably high, studies have shown that the return on investment often outweighs its cost [ 51 , 52 ]. Erecting barriers is proven to be a highly cost-effective and warranted suicide prevention strategy that is well recognized by the public.…”
Section: Discussionmentioning
confidence: 99%
“…It is time to integrate these clinical approaches into the conceptual framework for self-injury prevention grounded on the Haddon matrix. The costeffectiveness of installing physical barriers in bridges and cliffs to reduce suicides in these hotspots, as reported by Bandara and colleagues, 4 is especially instructive for developing and implementing engineering-and technology-based strategies aimed at environmental factors and major vectors carrying the etiologic agent, such as firearms and drugs, to reduce self-injury rates in the US.…”
mentioning
confidence: 97%
“…The stagnation in suicide prevention is not for lack of trying . In light of the ongoing COVID-19 pandemic, the worsening opioid crisis, and the rising prevalence of depression and other mental health problems, the study by Bandara and colleagues offers a glimmer of hope and a window of opportunity for rethinking suicide prevention.…”
mentioning
confidence: 99%
See 1 more Smart Citation